Analisis Strategi Harga dalam Hubungannya Dengan Kualitas Produk Studi Kasus Pada CV. Indonesia Printing - Magdalena, Annaria (Jurnal Ilmiah Ranggagading (JIR), 2010)
This purpose of this research is to find out price strategy policy done by CV. Indonesia Printing and its products quality yielded, its internal factors in the form of strengths and weaknesses, its external factors in the form of opportunities and threats, and also its barriers in connection with price strategy. The result shows that, at present, CV. Indonesia Printing gets growth/stability. The price strategy used is price determining based on produtcs quality yielded and adapted to the fuel that is used. Keywords: Price Strategy;